Perivascular epithelioid cell neoplasm (PEComa) of the urinary bladder presenting as urinary tract infection in a young woman - Dana Greenberg; Yoav Avidor; Rami Mattar; Muhammad Majdoub; Alona Meir; Ronen Rub (Urology Case Reports, 2024)
PEComa is a rare mesenchymal tumor with unique features, sometimes manifesting in younger patients and can exhibit malignant transformation. We present a 24-year-old woman with urinary symptoms and hematuria. Imagining revealed a protruding mass in the bladder dome, raising suspicion for adenocarcinoma due to its location and vascular appearance. Pathology revealed PEComa. Clinicians should inquire about macroscopic hematuria and assess the entire urinary tract even in young patients with apparent urinary tract infection. Practitioners should be mindful of PEComa tumors, especially in cases involving young patients with tumors concerning the bladder dome. A variety of immunohistochemical techniques facilitate the diagnosis.